The Influence of Media Exposure to the Final Presidential Debate Program in 2024 on Net TV Channel on the Attitudes of Voters in Jakarta - Putri, Amanda Kanary; Kinkin Yuliaty Subarsa Putri; Vera Wijayanti Sutjipto (Tecno Scientifica Publishing, 2024)
During elections, television is considered an important mass media platform for political campaigning by political parties. In general elections, it's undeniable that many political parties utilize mass media to influence the public. The lack of political awareness and education among first-time voters is feared to be a cause of declining political participation in the 2024 elections. Through the broadcast of presidential debates, prospective voters can learn about the vision, mission, and programs of presidential candidates. Over time, perceptions, both positive and negative, are formed. How candidate pairs convey messages and create impressions during debates is also observed. This research employs a quantitative approach using the survey method. The population consists of voters in Jakarta, with a sample size of 100 respondents determined using the Slovin formula. The study reveals a significant influence of media exposure from the final presidential debate program in 2024 on NET TV on the attitudes of voters in Jakarta, as confirmed by validity, reliability, and simple linear regression tests.